Pocket Kuala Lumpur : top sights, local life, made easy - Albiston, Isabel (Carlton, Victoria : Lonely Planet, 2017)
Lonely Planet Pocket Kuala Lumpur is your passport to the most relevant, up-to-date advice on what to see and skip, and what hidden discoveries await you. Take in the exhilarating views from the Petronas Towers, soak up the British colonial past in Merdeka Square, make a pilgrimage to the sacred Hindu site Batu Caves; all with your trusted travel companion. Get to the heart of the best of Kuala Lumpur and begin your journey now! Inside Lonely Planet Pocket Kuala Lumpur: ·Full-colour maps and images throughout ·Highlights and itineraries help you tailor your trip to your personal needs and interests ·Insider tips to save time and money and get around like a local, avoiding crowds and trouble spots ·Essential info at your fingertips - hours of operation, phone numbers, websites, transit tips, prices ·Honest reviews for all budgets - eating, sleeping, sight-seeing, going out, shopping, hidden gems that most guidebooks miss ·Free, convenient pull-out Kuala Lumpur map (included in print version), plus over 12 colour neighbourhood maps ·User-friendly layout with helpful icons, and organised by neighbourhood to help you pick the best spots to spend your time ·Covers Golden Triangle, Petronas Towers & KLCC, Chinatown & Merdeka Square, Masjid India, Chow Kit & Kampung Baru, Lake Gardens & Brickfields and more · The Perfect Choice: Lonely Planet Pocket Kuala Lumpur , a colorful, easy-to-use, and handy guide that literally fits in your pocket, provides on-the-go assistance for those seeking only the can't-miss experiences to maximize a quick trip experience. Looking for a comprehensive guide that recommends both popular and offbeat experiences, and extensively covers all of Kuala Lumpur's neighbourhoods? Check out Lonely Planet Kuala Lumpur, Melaka & Penang guide.
Includes index.
Keywords: Malaysia -- Kuala Lumpur; Kuala Lumpur (Malaysia) -- Description and travel; Kuala Lumpur (Malaysia) -- Guidebooks; Guidebooks; Guidebooks; Guidebooks